Ultra-thin overlay asphalt concrete and preparation method thereof

By using a combination of compacting agent, connecting reinforcement and water blocking agent in ultra-thin mask asphalt concrete, the problem of ultra-thin mask being susceptible to water erosion is solved, and its waterproof performance and connection strength are significantly improved.

CN116283068BActive Publication Date: 2025-02-14ZHANGQIU JINTONGDAO BRIDGE CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202310262210.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-03-17
Publication Date
2025-02-14
Estimated Expiration
2043-03-17

AI Technical Summary

Technical Problem

Ultra-thin overhead asphalt concrete is susceptible to water erosion, resulting in structural damage.

Method used

Using a combination of compacting agent, connecting reinforcement and water blocking agent, the compacting agent improves the compactness of concrete, the connecting reinforcement enhances waterproof performance, and reduces moisture erosion through water blocking agent.

Benefits of technology

It effectively improves the waterproof performance of the ultra-thin cover and the connection strength between the adhesive layer and the original pavement, reducing the impact of water erosion on the strength of the cover.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004131647840000071
    Figure BDA0004131647840000071
  • Figure BDA0004131647840000081
    Figure BDA0004131647840000081
  • Figure BDA0004131647840000091
    Figure BDA0004131647840000091
Patent Text Reader

Abstract

The present application relates to the field of asphalt concrete roads, and specifically discloses an ultra-thin overlay asphalt concrete and a preparation method thereof. The ultra-thin overlay asphalt concrete is composed of the following raw materials in parts by weight: 130 to 156 parts of coarse aggregate, 45 to 61 parts of fine aggregate, 5 to 13 parts of filler, 9 to 11 parts of asphalt, and 10 to 20 parts of reinforcing components, wherein the reinforcing components include a densifier, a connection enhancer, and a water-blocking agent, and the weight ratio of the densifier, the connection enhancer, and the water-blocking agent is 3 to 5:2 to 4:1. The ultra-thin overlay asphalt concrete of the present application can be used for ultra-thin overlay paving, and it has the advantages of strong water resistance and reducing damage to the ultra-thin overlay caused by water erosion.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of asphalt concrete roads, and more specifically, to an ultra-thin overlay asphalt concrete and a preparation method thereof. Background Art

[0002] Ultra-thin overlay is a functional overlay of asphalt pavement with a paving thickness of less than 25mm and a structural strength that meets the use requirements. As a preventive maintenance technology, ultra-thin overlay can effectively improve the noise reduction and anti-skid functions of the original pavement, while also preventing the development of cracks and water damage, and repairing rutting and other diseases, and is therefore widely used in the maintenance of various types of roads.

[0003] From the perspective of pavement structure and composition, the typical structure of ultra-thin overlay is also divided into original pavement, bonding layer with negligible actual thickness and overlay layer for wear. Compared with the ordinary overlay pavement structure, the thickness of the overlay layer is reduced, generally 1.5-2.0cm. Therefore, the ultra-thin overlay exhibits different characteristics from ordinary overlay pavement when subjected to external loads and environmental effects.

[0004] However, in actual applications, because the cover is thin, water can more easily enter the internal pores, making the cover more easily affected by water and damaged. Summary of the invention

[0005] In order to improve the water stability of concrete used for the overlay and reduce the degree of damage to the overlay, the present application provides an ultra-thin overlay asphalt concrete and a preparation method thereof.

[0006] In the first aspect, the present application provides an ultra-thin overlay asphalt concrete, which adopts the following technical solution:

[0007] An ultra-thin overlay asphalt concrete is composed of the following raw materials in parts by weight: 130 to 156 parts of coarse aggregate, 45 to 61 parts of fine aggregate, 5 to 13 parts of filler, 9 to 11 parts of asphalt, and 10 to 20 parts of reinforcing components, wherein the reinforcing components include a densifier, a connection reinforcing agent and a water-blocking agent, and the weight ratio of the densifier, the connection reinforcing agent and the water-blocking agent is 3 to 5:2 to 4:1.

[0008] By adopting the above technical scheme, the compaction degree of the overall asphalt concrete is improved by using a densifier, and the connection enhancer is used to improve the bonding strength between the water-blocking agent and the asphalt concrete, thereby improving the waterproof performance of the ultra-thin cover, and on the other hand, to increase the connection strength between the asphalt concrete and the bonding layer and the original pavement, thereby effectively reducing the impact of water erosion on the strength of the ultra-thin cover, thereby reducing the degree of damage to the cover caused by water erosion.

[0009] Preferably, the coarse aggregate includes three gradations of 7.1 mm to 9.5 mm, 4.75 mm to 7.1 mm and 2.36 mm to 4.75 mm, and the weight ratio of the three gradations is 3:10:1.

[0010] By adopting the above technical solution, the maximum particle size of the coarse aggregate is limited according to the properties of the ultra-thin cover, thereby effectively improving the construction stability and the cover stability.

[0011] Preferably, the oil-stone ratio is 5.2%.

[0012] By adopting the above technical solution, controlling the oil-stone ratio can effectively control the porosity of asphalt concrete and the thickness of the asphalt film, thereby effectively improving the water erosion resistance of the ultra-thin cover.

[0013] Preferably, the densifier comprises polyethylene and nano-hydroxyapatite, and the weight ratio of the polyethylene to the nano-hydroxyapatite is 9:1.

[0014] By adopting the above technical solution, nano-hydroxyapatite can effectively promote the solidification and crystallization of polyethylene, thereby effectively improving the density of ultra-thin overlay asphalt concrete, reducing the water entering the ultra-thin overlay, improving its waterproof performance, and effectively reducing the degree of damage to the ultra-thin overlay caused by water erosion.

[0015] Preferably, the connection enhancer comprises long-chain fatty acids, isomeric tridecanol polyoxyethylene ether and p-toluenesulfonic acid, and the weight ratio of the long-chain fatty acids, isomeric tridecanol polyoxyethylene ether and p-toluenesulfonic acid is 9:9:2.

[0016] By adopting the above technical scheme, the long-chain fatty acid plays a lubricating role, thereby making the isotridecyl alcohol polyoxyethylene ether and p-toluenesulfonic acid mixed more evenly in the concrete, and the isotridecyl alcohol polyoxyethylene ether is connected and solidified with the bonding layer, thereby increasing the connection strength between the isotridecyl alcohol polyoxyethylene ether and the bonding layer. At this time, the long-chain fatty acid and the isotridecyl alcohol polyoxyethylene ether react under the catalysis of p-toluenesulfonic acid, thereby further improving the connection strength between the isotridecyl alcohol polyoxyethylene ether and the ultra-thin cover, and effectively improving the connection strength between the bonding layer and the ultra-thin cover.

[0017] Preferably, the long-chain fatty acid is one of linoleic acid, linolenic acid or arachidonic acid.

[0018] By adopting the above technical solution, unsaturated fatty acids are selected to improve the water repellency of the connection enhancer, reduce the water entering between the adhesive layer and the ultra-thin cover, and further reduce the damage of water erosion to the ultra-thin cover.

[0019] Preferably, the water-blocking agent comprises chloroprene emulsion and nano-silicon dioxide, and the weight ratio of the chloroprene emulsion to the nano-silicon dioxide is 4:1.

[0020] By adopting the above technical solution, the mixed use of chloroprene emulsion and nano-silicon dioxide effectively improves the water resistance of asphalt concrete, thereby effectively reducing the damage of water erosion to the ultra-thin cover surface.

[0021] In a second aspect, the present application provides a method for preparing ultra-thin overlay asphalt concrete, using the following technical solution:

[0022] A method for preparing ultra-thin overlay asphalt concrete comprises the following steps: mixing coarse aggregate, fine aggregate and filler at 180° C. for 10 seconds, then adding asphalt, a densifier, a connection enhancer and a water-blocking agent and mixing at 160° C. for 2 minutes, and discharging the concrete after mixing.

[0023] By adopting the above technical solution, the dry materials are first mixed, and then raw materials such as asphalt are added to obtain asphalt concrete for paving ultra-thin overlays, which is simple and convenient to operate.

[0024] In summary, this application has the following beneficial effects:

[0025] 1. Since the present application uses a densifier to improve the overall density of asphalt concrete, and uses a connection enhancer to improve the bonding strength between the water-blocking agent and the asphalt concrete, thereby improving the waterproof performance of the ultra-thin cover, and on the other hand, to increase the connection strength between the asphalt concrete and the bonding layer and the original road surface, the effect of water erosion on the strength of the ultra-thin cover is effectively reduced, thereby reducing the degree of damage to the cover caused by water erosion.

[0026] 2. In the present application, the long-chain fatty acid plays a lubricating role, and the isotridecyl alcohol polyoxyethylene ether plays the role of connecting the adhesive layer and the ultra-thin cover. At this time, p-toluenesulfonic acid promotes the reaction of the long-chain fatty acid and the isotridecyl alcohol polyoxyethylene ether, further improving the connection strength between the adhesive layer and the ultra-thin cover.

[0027] 3. The long-chain fatty acids and isomeric tridecanol polyoxyethylene ether in the present application promote the solidification of polyethylene to a certain extent, thereby making the solidification of polyethylene improve the waterproof ability of asphalt concrete. DETAILED DESCRIPTION

[0028] In this application, the coarse aggregate is basalt aggregate, including three gradations of 7.1mm-9.5mm, 4.75mm-7.1mm and 2.36mm-4.75mm, and the weight ratio of the three gradations is 3:10:1; the fine aggregate is basalt aggregate, including 1.18mm-2.36mm, 0.6mm-1.18mm, 0.3mm-0.6mm, 0.15mm-0.3mm, 0.075mm-0.15mm, a total of five There are five gradations, and the weight ratio of the five gradations is 7.3:; the filler is ground limestone with a particle size of 325 mesh; the asphalt is SBS modified asphalt, which is purchased from the market; the polyethylene is purchased from the market; the particle size of nano hydroxyapatite is 60nm, which is purchased from the market; linoleic acid, linolenic acid or arachidonic acid are all purchased from the market; isomeric tridecyl alcohol polyoxyethylene ether is purchased from the market; p-toluenesulfonic acid is purchased from the market; chloroprene emulsion is purchased from the market; the particle size of nano silicon dioxide is 50nm, which is purchased from the market.

[0029] The present application is further described in detail below with reference to the embodiments.

[0030] Example

[0031] Example 1

[0032] This embodiment provides an ultra-thin overlay asphalt concrete, which is prepared by the following steps:

[0033] S1. Mix 130 kg of coarse aggregate, 45 kg of fine aggregate and 5 kg of filler at 180 °C for 10 seconds;

[0034] S2, add 10kg asphalt, 3.6kg polyethylene and 0.7kg nano-hydroxyapatite as densifiers, 1.8kg linoleic acid, 1.8kg isomeric tridecanol polyoxyethylene ether and 0.4kg p-toluenesulfonic acid as connection enhancers, and 1.6kg chloroprene emulsion and 0.4kg nano-silica as water-blocking agents, and stir and mix at 160°C for 2min;

[0035] S3, discharging after mixing is completed.

[0036] Example 2

[0037] This embodiment provides an ultra-thin overlay asphalt concrete, which is prepared by the following steps:

[0038] S1, 143kg coarse aggregate, 57kg fine aggregate and 9kg filler were mixed at 180℃ for 10s;

[0039] S2, add 11kg asphalt, 6.3kg polyethylene and 0.7kg nano-hydroxyapatite as densifiers, 2.7kg linoleic acid, 2.7kg isomeric tridecanol polyoxyethylene ether and 0.6kg p-toluenesulfonic acid as connection enhancers, and 1.6kg chloroprene emulsion and 0.4kg nano-silica as water-blocking agents, and stir and mix at 160°C for 2min;

[0040] S3, discharging after mixing is completed.

[0041] Example 3

[0042] This embodiment provides an ultra-thin overlay asphalt concrete, which is prepared by the following steps:

[0043] S1, 156kg coarse aggregate, 69kg fine aggregate and 13kg filler were mixed at 180℃ for 10s;

[0044] S2, add 12kg asphalt, 9kg polyethylene and 1kg nano hydroxyapatite as densifiers, 3.6kg linoleic acid, 3.6kg isomeric tridecanol polyoxyethylene ether and 0.8kg p-toluenesulfonic acid as connection enhancers, and 1.6kg chloroprene emulsion and 0.4kg nano silicon dioxide as water blocking agents, and stir and mix at 160°C for 2min;

[0045] S3, discharging after mixing is completed.

[0046] Example 4

[0047] This embodiment provides an ultra-thin overlay asphalt concrete, which is prepared by the following steps:

[0048] S1, 143kg coarse aggregate, 57kg fine aggregate and 9kg filler were mixed at 180℃ for 10s;

[0049] S2, add 11kg asphalt, 7kg polyethylene as a compacting agent, 2.7kg linoleic acid as a connection enhancer, 2.7kg isomeric tridecanol polyoxyethylene ether and 0.6kg p-toluenesulfonic acid, and 1.6kg chloroprene emulsion as a water-blocking agent and 0.4kg nano-silica, and stir and mix at 160°C for 2min;

[0050] S3, discharging after mixing is completed.

[0051] Example 5

[0052] This embodiment provides an ultra-thin overlay asphalt concrete, which is prepared by the following steps:

[0053] S1, 143kg coarse aggregate, 57kg fine aggregate and 9kg filler were mixed at 180℃ for 10s;

[0054] S2, add 11kg asphalt, 6.3kg polyethylene and 0.7kg nano-hydroxyapatite as densifiers, 2.7kg linolenic acid, 2.7kg isomeric tridecanol polyoxyethylene ether and 0.6kg p-toluenesulfonic acid as connection enhancers, and 1.6kg chloroprene emulsion and 0.4kg nano-silica as water-blocking agents, and stir and mix at 160°C for 2min;

[0055] S3, discharging after mixing is completed.

[0056] Example 6

[0057] This embodiment provides an ultra-thin overlay asphalt concrete, which is prepared by the following steps:

[0058] S1, 143kg coarse aggregate, 57kg fine aggregate and 9kg filler were mixed at 180℃ for 10s;

[0059] S2, add 11kg asphalt, 6.3kg polyethylene and 0.7kg nano-hydroxyapatite as densifiers, 2.7kg arachidonic acid, 2.7kg isomeric tridecanol polyoxyethylene ether and 0.6kg p-toluenesulfonic acid as connection enhancers, and 1.6kg chloroprene emulsion and 0.4kg nano-silica as water-blocking agents, and stir and mix at 160°C for 2min;

[0060] S3, discharging after mixing is completed.

[0061] Example 7

[0062] This embodiment provides an ultra-thin overlay asphalt concrete, which is prepared by the following steps:

[0063] S1, 143kg coarse aggregate, 57kg fine aggregate and 9kg filler were mixed at 180℃ for 10s;

[0064] S2, add 11kg asphalt, 6.3kg polyethylene and 0.7kg nano-hydroxyapatite as densifiers, 5.4kg linoleic acid and 0.6kg p-toluenesulfonic acid as connection enhancers, and 1.6kg chloroprene emulsion and 0.4kg nano-silica as water-blocking agents, and stir and mix at 160°C for 2min;

[0065] S3, discharging after mixing is completed.

[0066] Example 8

[0067] This embodiment provides an ultra-thin overlay asphalt concrete, which is prepared by the following steps:

[0068] S1, 143kg coarse aggregate, 57kg fine aggregate and 9kg filler were mixed at 180℃ for 10s;

[0069] S2, add 11kg asphalt, 6.3kg polyethylene and 0.7kg nano-hydroxyapatite as densifiers, 5.4kg isomeric tridecanol polyoxyethylene ether and 0.6kg p-toluenesulfonic acid as connection enhancers, and 1.6kg chloroprene emulsion and 0.4kg nano-silica as water-blocking agents, and stir and mix at 160°C for 2min;

[0070] S3, discharging after mixing is completed.

[0071] Example 9

[0072] This embodiment provides an ultra-thin overlay asphalt concrete, which is prepared by the following steps:

[0073] S1, 143kg coarse aggregate, 57kg fine aggregate and 9kg filler were mixed at 180℃ for 10s;

[0074] S2, add 11kg of asphalt, 6.3kg of polyethylene and 0.7kg of nano-hydroxyapatite as densifiers, 2.7kg of linoleic acid, 2.7kg of isotridecyl polyoxyethylene ether and 0.6kg of p-toluenesulfonic acid as connection enhancers, and 2kg of chloroprene emulsion as a water-blocking agent, and stir and mix at 160°C for 2min;

[0075] S3, discharging after mixing is completed.

[0076] Example 10

[0077] This embodiment provides an ultra-thin overlay asphalt concrete, which is prepared by the following steps:

[0078] S1, 143kg coarse aggregate, 57kg fine aggregate and 9kg filler were mixed at 180℃ for 10s;

[0079] S2, add 11kg of asphalt, 6.3kg of polyethylene and 0.7kg of nano-hydroxyapatite as densifiers, 2.7kg of linoleic acid, 2.7kg of isomeric tridecanol polyoxyethylene ether and 0.6kg of p-toluenesulfonic acid as connection enhancers, and 2kg of nano-silica as a water-blocking agent, and stir and mix at 160°C for 2min;

[0080] S3, discharging after mixing is completed.

[0081] Embodiment 11

[0082] This embodiment provides an ultra-thin overlay asphalt concrete, which is prepared by the following steps:

[0083] S1, 143kg coarse aggregate, 57kg fine aggregate and 9kg filler were mixed at 180℃ for 10s;

[0084] S2, add 10kg asphalt, 6.3kg polyethylene and 0.7kg nano-hydroxyapatite as densifiers, 2.7kg linoleic acid, 2.7kg isomeric tridecanol polyoxyethylene ether and 0.6kg p-toluenesulfonic acid as connection enhancers, and 1.6kg chloroprene emulsion and 0.4kg nano-silica as water-blocking agents, and stir and mix at 160°C for 2min;

[0085] S3, discharging after mixing is completed.

[0086] Example 12

[0087] This embodiment provides an ultra-thin overlay asphalt concrete, which is prepared by the following steps:

[0088] S1, 143kg coarse aggregate, 57kg fine aggregate and 9kg filler were mixed at 180℃ for 10s;

[0089] S2, add 12kg asphalt, 6.3kg polyethylene and 0.7kg nano-hydroxyapatite as densifiers, 2.7kg linoleic acid, 2.7kg isomeric tridecanol polyoxyethylene ether and 0.6kg p-toluenesulfonic acid as connection enhancers, and 1.6kg chloroprene emulsion and 0.4kg nano-silica as water-blocking agents, and stir and mix at 160°C for 2min;

[0090] S3, discharging after mixing is completed.

[0091] Comparative Example

[0092] Comparative Example 1

[0093] This comparative example provides an ultra-thin overlay asphalt concrete, which is different from Example 2 in that no densifier is added.

[0094] Comparative Example 2

[0095] This comparative example provides an ultra-thin overlay asphalt concrete, which is different from Example 2 in that no connection enhancer is added.

[0096] Comparative Example 3

[0097] This comparative example provides an ultra-thin overlay asphalt concrete, which is different from Example 2 in that no water-blocking agent is added.

[0098] Comparative Example 4

[0099] This comparative example provides an ultra-thin overlay asphalt concrete, which is different from Example 2 in that no densifier and connection enhancer are added.

[0100] Comparative Example 5

[0101] This comparative example provides an ultra-thin overlay asphalt concrete, which is different from Example 2 in that no densifier and water-blocking agent are added.

[0102] Comparative Example 6

[0103] This comparative example provides an ultra-thin overlay asphalt concrete, which is different from Example 2 in that no connection enhancer and water-blocking agent are added.

[0104] Comparative Example 7

[0105] This comparative example provides an ultra-thin overlay asphalt concrete, which is different from Example 2 in that no densifier, connection enhancer and water-blocking agent are added.

[0106] Table 1 Examples and Comparative Examples Raw Materials (kg)

[0107]

[0108]

[0109] Performance testing

[0110] Test items:

[0111] 1. Referring to JTGE20-2011 "Test Procedures for Asphalt and Asphalt Mixtures for Highway Engineering", the asphalt concretes prepared in the examples and comparative examples were subjected to a water-immersion Marshall test, respectively, at 60°C for 30 min, to test the residual stability of the water immersion.

[0112] 2. Pull-out test: first use the asphalt concrete prepared in comparative example 7 as the pavement layer, then spread the emulsified asphalt tack coat PC-3 on the pavement layer, and then lay the asphalt concrete prepared in the embodiment or comparative example on the tack coat as an ultra-thin cover with a thickness of 1 cm. After curing, take a core sample for a pull-out test. The core sample diameter is 100 mm, the pull-out test temperature is 25°C, and the core sample insulation time is 4 h.

[0113] 3. Drill core samples based on the construction of Test 2 and test the water permeability coefficient of the core samples.

[0114] Table 2 Performance test data table

[0115]

[0116] From Example 2 and Comparative Examples 1-7 and Table 2, it can be seen that the compaction agent is used to improve the overall compactness of the asphalt concrete, and the connection enhancer is used to improve the bonding strength between the water-blocking agent and the asphalt concrete, thereby improving the waterproof performance of the ultra-thin cover, and on the other hand, the connection strength between the asphalt concrete and the bonding layer and the original pavement is increased, effectively reducing the effect of water erosion on the strength of the ultra-thin cover, thereby reducing the degree of damage to the cover caused by water erosion.

[0117] From Example 2 and Example 4 and Table 2, it can be seen that nano-hydroxyapatite can effectively promote the solidification and crystallization of polyethylene, thereby effectively improving the density of ultra-thin overlay asphalt concrete, reducing the water entering the ultra-thin overlay, improving its waterproof performance, and effectively reducing the degree of damage to the ultra-thin overlay caused by water erosion.

[0118] It can be seen from Example 2, Examples 5-8 and Table 2 that the long-chain fatty acid acts as a lubricant, thereby making the isomeric tridecanol polyoxyethylene ether and p-toluenesulfonic acid mix more evenly in the concrete, and the isomeric tridecanol polyoxyethylene ether is connected and solidified with the bonding layer, thereby increasing the connection strength between the isomeric tridecanol polyoxyethylene ether and the bonding layer. At this time, the long-chain fatty acid and the isomeric tridecanol polyoxyethylene ether react under the catalysis of p-toluenesulfonic acid, thereby further improving the connection strength between the isomeric tridecanol polyoxyethylene ether and the ultra-thin cover, effectively improving the connection strength between the bonding layer and the ultra-thin cover, and selecting linoleic acid on this basis again to further improve the connection strength and waterproof performance.

[0119] It can be seen from Example 2, Example 9 and Example 10 and Table 2 that the use of unsaturated fatty acids can improve the water repellency of the connection enhancer, reduce the water entering between the adhesive layer and the ultra-thin cover, and further reduce the damage of water erosion to the ultra-thin cover.

[0120] It can be seen from Example 2, Example 11 and Example 12 and Table 2 that controlling the oil-stone ratio can effectively control the porosity and asphalt film thickness of the asphalt concrete, thereby effectively improving the water erosion resistance of the ultra-thin cover.

[0121] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. An ultra-thin overlay asphalt concrete, characterized in that: The invention is composed of the following raw materials in parts by weight: 130 to 156 parts of coarse aggregate, 45 to 61 parts of fine aggregate, 5 to 13 parts of filler, 9 to 11 parts of asphalt, and 10 to 20 parts of reinforcing components, wherein the reinforcing components include a densifier, a connection reinforcing agent, and a water-blocking agent, and the weight ratio of the densifier, the connection reinforcing agent, and the water-blocking agent is 2 to 5:2 to 4:1; The compacting agent comprises polyethylene and nano-hydroxyapatite, and the weight ratio of the polyethylene to the nano-hydroxyapatite is 9:1; The connection enhancer comprises long-chain fatty acid, isomeric tridecanol polyoxyethylene ether and p-toluenesulfonic acid, and the weight ratio of the long-chain fatty acid, isomeric tridecanol polyoxyethylene ether and p-toluenesulfonic acid is 9:9:

2.

2. The ultra-thin overlay asphalt concrete according to claim 1, characterized in that: The coarse aggregate includes three gradations of 7.1 mm to 9.5 mm, 4.75 mm to 7.1 mm and 2.36 mm to 4.75 mm, and the weight ratio of the three gradations is 3:10:

1.

3. The ultra-thin overlay asphalt concrete according to claim 1, characterized in that: The oil-to-stone ratio is 5.2%.

4. The ultra-thin overlay asphalt concrete according to claim 1, characterized in that: The long-chain fatty acid is one of linoleic acid, linolenic acid or arachidonic acid.

5. The ultra-thin overlay asphalt concrete according to claim 1, characterized in that: The water-blocking agent comprises chloroprene emulsion and nano-silicon dioxide, and the weight ratio of the chloroprene emulsion to the nano-silicon dioxide is 4:

1.

6. The method for preparing the ultra-thin overlay asphalt concrete according to any one of claims 1 to 5, characterized in that: The following steps are involved: The coarse aggregate, fine aggregate and filler were mixed and stirred at 180°C for 10 seconds, and then asphalt, densifier, connection enhancer and water barrier agent were added and stirred at 160°C for 2 minutes. After mixing, the materials were discharged.

Citation Information

Patent Citations

  • High-ductility elastic ultrathin overlay asphalt mixture, paving method of asphalt mixture and paved high-ductility and ultra-thin overlay

    CN113292274A

  • EME-14 high-modulus asphalt concrete and preparation method thereof

    CN114804726A

  • Fair-faced concrete and production process thereof

    CN115073085A